EVALUASI PENERAPAN PERLAKUAN AKUNTANSI TERHADAP AKTIVA TETAP BERDASARKAN PSAK NO 16 PADA PT. PEGADAIAN ( PERSERO ) CABANG MALALAYANG MANADO - Hariadi, Muhammad Bahari; Nangoi, Grace B.; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Company is organization that has certain activities to achieve the objectives charged to him. Each company has a goal to be achieved, both short-term and long-term, that is to gain profit and increase the company's profit. A goal will be achieved if a company is well managed and supported by means that can help achieve the goal. One of the supporting facilities used to achieve these objectives is fixed assets. Fixed Asset is a very important company asset, without a fixed asset it is impossible for a company to use its regular operational activities properly according to the Indonesian Accounting Association (2015: 16), Fixed assets are tangible properties held for use in the production or supply of goods or services to other parties or for administrative purposes and is expected to be used for more than one period. Fixed assets are company assets whose period of use is more than one accounting normal period (usually one year of use). Property assets belonging to fixed assets, ie land, buildings, machinery (mechines), vehicles, copyrights and so on. The Company's fixed assets are obtained through various means, among other things, by cash purchase, credit purchase, purchase with securities, exchange, obtained from prizes or donations and built on their own. Because of its long age, the assets are still needed as an investment so that the company is able to manage effectively and efficiently. as time goes by, the benefits of fixed assets will generally decrease continuously, leading to depreciation. All fixed assets may experience depreciation except land. Depreciation calculations are usually based on management policy in accordance with commonly used methods. Based on the description above, very interested to discuss more deeply about fixed assets. This prompted the authors for the final compilers entitled "Evaluation Of Accounting Treatment On Earning Asset Based On Financial Accounting Standard Number 16 At PT Pegadaian (Persero).